CHARACTERIZATION OF A CONTINUOUS, VERY NARROWBAND SEISMIC SIGNAL NEAR 2.08 HZ - Liu K.H.; Gao S.S. (My University, 2001)
We have detected a continuous seismic signal near 2.08 Hz using data from a portable seismic array, 1280 km long, deployed in Siberia and Mongolia. The signal can be observed on almost all the stations along the profile. The amplitude and the frequency of the signal show a clear daily cycle, and their temporal variations are similar at different stations, suggesting that the signals observed at different stations have a common source. We performed a nonlinear inversion of the amplitude of the signal and found that the geometrical-spreading factor is about 0.6, implying that the signal is most likely to be a form of surface waves. The source location found by the inversion is in the vicinity of the city of Irkutsk, which is about 50 km north of Lake Baikal.